2021
DOI: 10.3390/geriatrics7010006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nursing Staffs’ Working Conditions on the Quality of Care Received by Older Adults in Long-Term Residential Care Facilities: A Systematic Review of Interventional and Observational Studies

Abstract: Background: Little documentation exists on relationships between long-term residential care facilities (LTRCFs), staff working conditions and residents’ quality of care (QoC). Supporting evidence is weak because most studies examining this employ cross-sectional designs. Methods: Systematic searches of twelve bibliographic databases sought experimental and longitudinal studies, published up to May 2021, focusing on LTRCF nursing staff’s working conditions and the QoC they provided to older adults. Results: Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This study resulted in nurses reporting high intent to stay in their current work organization, in long-term care, and generally in nursing. This report of a favorable perception of the nurse practice environment and a high degree of intent to stay among nurses in long-term care was surprising because it contradicts the general perception of poor working conditions (Perruchoud et al, 2021) and the high rate of nurse turnover in long-term care (Gandhi et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study resulted in nurses reporting high intent to stay in their current work organization, in long-term care, and generally in nursing. This report of a favorable perception of the nurse practice environment and a high degree of intent to stay among nurses in long-term care was surprising because it contradicts the general perception of poor working conditions (Perruchoud et al, 2021) and the high rate of nurse turnover in long-term care (Gandhi et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…This study resulted in nurses reporting high intent to stay in their current work organization, in long‐term care, and generally in nursing. This report of a favorable perception of the nurse practice environment and a high degree of intent to stay among nurses in long‐term care was surprising because it contradicts the general perception of poor working conditions (Perruchoud et al., 2021) and the high rate of nurse turnover in long‐term care (Gandhi et al., 2021). Notable nurses' characteristics in this group include a high median age (40.5 years) and extensive work experience (10 years of work experience as a nurse, 3.6 years working in their current facility, and 8.7 years working in long‐term care).…”
Section: Discussionmentioning
confidence: 88%
“…The association between staffing shortages and adverse resident outcomes is very well documented in the pre-pandemic and pandemic literature. For example, a 2022 systematic review of 11 research papers found that increased nursing hours per resident per day were associated with a statistically significant reduction in adverse resident outcomes such as pressure ulcers and urinary tract infections [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also assessed the impact of the CLE in LTC with other scales [15], also finding moderate positive results. It might appear paradoxical that in a clinical setting with worse nurse-patient ratios and a lack of resources [42,43] students rate the CLE as positive. The interpretation of this data might take into consideration various aspects.…”
Section: Discussionmentioning
confidence: 99%